BENTUK PENYAJIAN KOMPANG PADA PESTA PERKAWINAN DALAM PROSESI ARAK-ARAKAN MASYARAKAT MUARA JANGGA - Dewi Martha; Syeilendra Syeilendra; Marzam Marzam (SENDRATASIK UNP, 2013)
Abstract This research was aimed at describing the form of Kompang art performed at a wedding ceremony in Muara Jangga. This research was a qualitative one with data collected through a literary studi, observation, interviews, documentations, recordings and photographs. The data analysis was classified into two that were primary data and secondary data which were designed systematically. The result of the research has shown that Kompang was performed in the form of Islamic songs assisted by Kompang music instruments. The song lyrics were taken from Nadzom (Al-barzanji). Kompang performed at the wedding ceremony was a kind of music ensamble played by men which escorts the bride and groom parade to the place where the wedding party would be held.   Kata Kunci: Bentuk Penyajian, Kompang, Pesta Perkawinan, Prosesi Arak-arakan , Muara Jangga